Merawat Kesehatan Mental Melalui Mindfulness dan Dukungan Sosial pada Dharma Wanita Balai Taman Nasional Alas Purwo - Yanuar Fahmi Pamungkas, Akhmad; Roudlotun Nurul Laili; Dian Roshanti (Journal of Health Innovation and Community Services, 2025)
Mental health is a crucial aspect of well-being that often receives less attention, particularly among women who hold multiple roles as wives, mothers, and members of organizations. The Dharma Wanita of Balai Taman Nasional Alas Purwo represents a strategic group in promoting mental health awareness, as their activities not only focus on domestic responsibilities but also support institutional functions. This community service program aimed to provide education, skills, and guidance in maintaining mental health through interactive learning and relaxation practices. The methods applied included lectures using multimedia presentations, focused group discussions, and training in simple relaxation techniques with a mindfulness-based approach. The program was carried out in a participatory manner, encouraging active involvement of participants through questions, sharing experiences, and collective practice. The results indicated an improvement in participants’ knowledge regarding mental health concepts, stress-triggering factors, and practical strategies for managing emotions and daily pressures. Participants also reported experiencing greater calmness, increased motivation, and stronger social support among members. Furthermore, the program succeeded in building collective awareness of the importance of mental health as a foundation for family harmony and organizational sustainability. In conclusion, this community service activity not only generated positive impacts at the individual level but also strengthened the role of Dharma Wanita in fostering a healthy, productive, and harmonious environment.